Catalytic Enantioselective Synthesis of Chiral Isatin Derivatives by an Aldol Approach - Yanagisawa, Akira; Kushihara, Naoyuki; Sugita, Takuya; Yoshida, Kazuhiro (Synlett, 2012)
A catalytic enantioselective aldol reaction of alkenyl esters with isatins was achieved using an (S)-BINOL-derived chiral tin dibromide possessing a 4-tert-butylphenyl group at 3- and 3′-positions as the chiral pre-catalyst in the presence of sodium methoxide and methanol. Optically active 3-alkylated 3-hydroxy-2-oxindoles having up to 98% ee were diastereoselectively obtained in high yields not only from cyclic alkenyl esters but also from acyclic ones under the influence of the in situ generated chiral tin bromide methoxide.
Keywords: aldol reaction; alkenyl ester; asymmetric catalysis; isatin; tin